Laetisaria fuciformis (Basidiomycota, Corticiaceae), nuevo registro de un parásito fúngico sobre gramíneas en el sur de Chile - Palfner, Götz; Marticorena, Alicia; Medina, Marcelo (Gayana Botánica, 2010)
A new record of the fungal grass parasite Laetisaria fuciformis from southern Chile is described and its biology is briefly discussed.